How do you solve x – y = 3 and 2x + 2y = 2?

2 Answers
Jun 14, 2018

(x,y)=(2,-1)

Explanation:

From the first equation, x=y+3. Substitute in to the second:
2(y+3)+2y=2. Multiply this out: 2y+6+2y=2. Collect terms: 4y=-4, so y=-1.

Return to the first equation: x-(-1)=3, so x=2.

Jun 14, 2018

(x,y)to(2,-1)

Explanation:

x-y=3to(1)

2x+2y=2to(2)

"from equation "(1)tox=3+yto(3)

"substitute "x=3+y" into equation "(2)

2(3+y)+2y=2

6+2y+2y=2

"subtract 6 from both sides"

4y=-4rArry=(-4)/4=-1

"substitute "y=-1" into equation "(3)

x=3-1=2

"point of intersection "=(2,-1)
graph{(y-x+3)(y+x-1)=0 [-10, 10, -5, 5]}